FOREIGN BODIES IN THE ANORECTAL AREA (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
Foreign bodies are rare in the rectum of children. It is often the result of ingesting bodies along the entire digestive tract from standing in the rectum, or sometimes foreign bodies are formed in the same place (sticking of fruit grains and garbage stones). In rare cases, sharp foreign bodies can be penetrated into the pararectal tissue through the posterior passage.